How to train your dragon book 11 : how to betray a dragon$1 (Bs hero /s - Cowell, Cressida (New York : Little, Brown and Company, 2014)
With the Doomsday of Yule approaching, Hiccup Horrendous Haddock III faces betrayal, peril, and the greatest challenge yet as he seeks to unite humans and dragons before it is too late.
Originally published in the U.K. by Hodder Children$1 (Bs Books, 2013.s
Keywords: Vikings -- Fiction; Dragons -- Fiction; Betrayal -- Fiction; Quests (Expeditions) -- Fiction; Friendship -- Fiction; Fathers and sons -- Fiction; Humorous stories